Implementation of Smart Tourism in Kedang Ipil Village - Kezia Arum Sary; Silviana Purwanti; Rina Juwita (Budapest International Research and Critics University, 2021)
Information communication technology nowadays is used in the economic era digital and tourism industry. Related to ecotourism is applying intelligent tourist villages, preserving natural resources, maintaining physical and mental health, and providing a positive response to the surrounding community. Not fully utilized by online media. Compete globally but able to take advantage of information technology. This research aims to see the village's concern and readiness to use information technology to realize smart tourism. The qualitative research method used interviews of all managers of Kedang Ipil Village. The results showed that the Kedang Village manager used social media to introduce and even sell the old Kutai traditions through Facebook, website and Instagram.